The silver chalice - Samuels, Lesser; Saville, Victor; Victor Seville Production; Warner Brothers Pictures ([Burbank, Calif.] Warner Home Video, 1954)
Biblical saga about a young Greek artisan who is commissioned to design a chalice for the cup Christ used at the Last Supper.
VHS
From the novel by Thomas B. Costain.
Film editor, George White; music composed and conducted by Franz Waxman.
Virginia Mayo, Pier Angel, Jack Palance, Paul Newman.
Keywords: Feature films